Proposta de enquadramento para a bacia hidrográfica do arroio Jacutinga, município de Ivorá-RS - Binotto, Diego (2012)
The objective of this research was to suggest the proposed classification of bodies of water to the basin of the stream Jacutinga, city of Ivorá-RS, based in its water usage and current status of water quality. The stream Jacutinga and its tributaries have been widely used for the irrigation of vegetables and fruit trees, watering animals, receiving and dilutive of effluents released partially untreated sewage discharge and the station sewage treatment. To evaluate the water quality to the basin of the stream Jacutinga, we used 8 points for water quality sampling and flow measurement in the period January 2009 to February 2011, totaling 6 campaigns. Analyses of physical, chemical and biological water were carried out, comparing the quality to the standards established by CONAMA Resolution 357/05. Therefore, analyzing the current situation of the body of water has the objective to evaluate the potential of water bodies to be classified to meet the water use and consequently class of classification. This classification allows to determine how much the waters are impacted by pollution and what are the critical variables. With regard to the current situation of water quality, the variables turbidity, pH, TDS and BOD were within the limits from class 1 in all sampling points. DO was within limits of class 1, except at the sampling point QA4, which was within the limits of class 2. Escherichia coli variable was within the limits of class 2, except at the sampling point QA7, where you stayed within the limits of class 1 and sampling point QA5, where it stayed within the limits of class 3. The suggestion of proposed classification of bodies of water to the basin of the stream Jacutinga based on water uses and current status of quality water, would be to conduct mitigating measures in point area sampling QA5, so that its waters remain within the limits of class 2, through the deployment of domestic sewage network in the stretch that includes the sampling points QA3-QA4 linking of station sewage treatment.